Pengembangan Media Pembelajaran Bangun Ruang Berbasis GeoGebra untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SD - Aprilia, Della; Zainil, Melva (Universitas Negeri Padang, 2022)
This study aims to produce GeoGebra space learning media for elementary school students. This type of research is a research development with the ADDIE model, namely Analysis (analysis), Design (design), Development (Development), Implementation (implementation), and Evaluation (evaluation). The results of this study are: 1) The author has produced GeoGebra learning media for Geometric fifth grade SD which is valid with a validity of 90% 2) The author has produced GeoGebra learning media for Geometric fifth grade SD wich is practice with 89.29% practicality from the teacher's response and 91.36% of the students' responses, 3) The author has produced GeoGebra learning media for Geometric fifth grade SD wich is effective with an increase percentage of 85,15% and completeness of 88,89%.